Combined Fluorescence-Guided Surgery and Photodynamic Therapy for Glioblastoma Multiforme Using Cyanine and Chlorin Nanocluster. (16th November 2020) - Teng, Clare W; Amirshaghaghi, Ahmad; Cho, Steve S; Cai, Shuting; De Ravin, Emma; Singh, Yash; Miller, Joann; Sheikh, Saad; Delikatny, Jim; Cheng, Zhiliang; Busch, Theresa; Singhal, Sunil; et al.
Abstract: INTRODUCTION: Glioblastoma multiforme (GBM) is the most common, yet the deadliest, form of primary brain tumor. Survival can be improved by amplifying the extent of resection or eliminating residual tumor cells post-operatively. Here, we combined a near-infrared dye (Indocyanine-Green, ICG) and a photosensitizer (Chlorin-e6, Ce6), two Food and Drug Administration (FDA) approved components, into a single nanocluster (ICS) to enable both fluorescence-guided resection and photodynamic therapy (PDT) of residual disease. METHODS: A murine flank tumor model was adopted to evaluate NIR fluorescence-guided surgery and PDT efficacy of ICS in vivo. Female C57BL/6 mice underwent subcutaneous injections of 4 × 10 6 GL261-luciferase cells in the flank. 5mg/kg of ICS was administered intravenously 24hours prior to NIR imaging. Partial tumor resections were performed under NIR fluorescence, leaving a small positive margin of disease. Post-resection, half the animals injected with ICS were randomly selected to receive PDT. Tumor progression was compared between the PDT and control groups. RESULTS: ICS demonstrated a high ICG and Ce6 encapsulation efficiency, a high payload capacity, and chemical stability both in vitro and in physiologic conditions. Cell culture studies demonstrated comparable PDT effects to Ce6 using ICS. Preclinical animal studies demonstrated that the nanoclusters can be detected through NIR fluorescence imaging in both syngeneic flank and orthotopic GBM tumors at 745nm excitation (mean signal-to-background of 8.5 ± 0.57). In the tumor recurrence study following partial-resection, mice that received PDT demonstrated significantly reduced tumor size compared to non-irradiated controls on days 8 (23.1mm 3 vs 150.5mm 3, P -value = 0.045) and later on day 23 (220.4mm 3 vs 806.1mm 3, P -value = 0.0055). CONCLUSION: We built a multimodal theragnostic agent comprised solely of FDA-approved components that allows for both optical imaging and PDT. The findings demonstrate robust evidence for the potential theragnostic benefit of ICS in surgical oncology.